2013
DOI: 10.1016/j.appet.2013.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Slimming starters. Intake of a diet-congruent food reduces meal intake in active dieters

Abstract: Dietary restraint is known to break down in the face of tempting foods. Previous research suggests exposure to cues associated with slimming such as images or odours act as prompts to restrict intake of a tempting snack in dieters. The effects of consuming diet-congruent foods on subsequent intake of a meal have not yet been investigated. Thus, using a repeated measures design 26 female participants (dieters or non-dieters) consumed a diet-congruent (100 kcal salad), hedonic (100 kcal garlic bread) or neutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…For example, future work may apply the platform to improve understanding about the determinants of perceived satiating capacity. This has relevance considering the potential consumer benefits of satiety enhancing foods (Hetherington et al, 2013). Furthermore, research might examine food perceptions under different environmental and physiological conditions, such as how packaging or branding (Cavanagh et al 2014), portion size (Piqueras-Fiszman, Harrar, Alcaide, & Spence, 2011) or nutritional status (Cabanac, 1979;Frank et al 2010) affects food perceptions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, future work may apply the platform to improve understanding about the determinants of perceived satiating capacity. This has relevance considering the potential consumer benefits of satiety enhancing foods (Hetherington et al, 2013). Furthermore, research might examine food perceptions under different environmental and physiological conditions, such as how packaging or branding (Cavanagh et al 2014), portion size (Piqueras-Fiszman, Harrar, Alcaide, & Spence, 2011) or nutritional status (Cabanac, 1979;Frank et al 2010) affects food perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions about foods can also reduce food intake. Buckland, et al (2013) found that eating food perceived to be congruent with weight loss goals -caloric food associated with hedonic goals. As perceptions of food play a role in the choice and amount of food consumed, it could be valuable to systematically explore which common dimensions of foods contribute to the strength of consumer perceptions to facilitate healthy eating choices.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Seeing or consuming healthy foods has been shown to reduce intake of unhealthy foods, mostly among dieters (Buckland, Finlayson, & Hetherington, 2013a, 2013b; Buckland, Finlayson, Edge, & Hetherington, 2014). Similarly, health primes such as dieting advertisements, compared to control or indulgent food advertisements, can prevent overeating on unhealthy foods, again especially among dieters, and especially in the afternoon (Anschutz, Van Strien, & Engels, 2011; Boland, Connell, & Vallen, 2013; Versluis & Papies, 2016).…”
Section: Interventions To Affect Nonconscious Regulation Of Health Bementioning
confidence: 99%
“…Buckland et al [45] demonstrated that a diet-congruent starter (e.g., a salad) was associated with a significant reduction in EI at lunch when compared with a hedonic starter (e.g., garlic bread) in dieters. The labelling manipulation thus likely had reduced impact on the cookies because they are not a diet-congruent food item.…”
Section: Discussionmentioning
confidence: 99%